Learning circular motion with the demonstration method using the problem-based learning model to improve physics learning outcomes - Az-Zahra, Lumenia; Ismail, Ali (Insitut Pendidikan Indonesia, 2024)
This study aims to improve students’ learning outcomes on the topic of circular motion through the application of the demonstration method using the Problem-Based Learning (PBL) model. The research was conducted at a public high school in Garut. The research method used was an experimental approach with a Pretest-Post test Control Group design. The sample was selected using purposive sampling, consisting of one experimental class that applied the demonstration method with the PBL model and one control class that used conventional methods. The instrument used was an essay test comprising six questions. The results showed that the demonstration method with the PBL model led to a significant improvement in students’ learning outcomes compared to conventional methods. The average pretest score of the experimental class increased from 26.34 to 70.51 in the post-test, while the control class increased from 26.54 to 58.54. Based on the t-test results, the implementation of the demonstration method with PBL was more effective in enhancing students’ learning outcomes on the topic of circular motion.